2008
DOI: 10.1097/btf.0b013e31818f3505
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the Painful Forefoot

Abstract: Imaging of the painful forefoot has advanced rapidly in the previous 20 years, with the development of magnetic resonance (MR) imaging and dynamic musculoskeletal ultrasound (MSKUS). Each modality has its strengths and weaknesses, as outlined later. Diagnoses are made at the time of the MSKUS scan and images are taken to demonstrate any abnormality, whereas MR diagnoses are made from a predetermined series of image sequences. Musculoskeletal ultrasound has the advantage of clinical input, whereas MR images are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…2). Previous studies have reported interdigital nerves within neuromas (39); however, we could not visualize nerves using US. Edema, axonal degeneration, and fibrosis can affect echogenicity and elasticity.…”
Section: Discussionmentioning
confidence: 68%
“…2). Previous studies have reported interdigital nerves within neuromas (39); however, we could not visualize nerves using US. Edema, axonal degeneration, and fibrosis can affect echogenicity and elasticity.…”
Section: Discussionmentioning
confidence: 68%
“…In cases of interdigital neuroma, an increased transverse relaxation time (T2) signal, greater calibration, and increased contrast uptake may be seen on MRI due to the affected interdigital nerve. Some authors have also reported a relationship between neuroma and the interdigital nerve (Simmons, 2008;Waizy et al, 2010). The term "target sign" is used for central hypointense and peripheral hyperintense-looking round tumors derived from neural tissue (Bhargava et al, 1997).…”
Section: Slavinmentioning
confidence: 99%
“…The extruding content may be formed by the MN and/or the bursa. It is theorized that the click will only happen when there is a MN because a thickened bursa is much more pliable than a neuroma[ 16 ]. As both entities may coexist, we can complete the US scan with another maneuver that will help in differentiating between MN and bursal tissue.…”
Section: Imaging Of Mnmentioning
confidence: 99%